Proteomic Analysis of Cerebrospinal Fluid: A Search for Biomarkers of Neuropsychiatric Systemic Lupus Erythematosus - Pedroza-Díaz, Johanna; Chavarria, Tania Paola Luján; Vahos, Carlos Horacio Muñoz; Hernández Ramírez, Diego F.; Olivares-Martínez, Elizabeth; Vásquez, Gloria; Llorente, Luis; Fragoso-Loyo, Hilda; Röthlisberger, Sarah; Ortiz Reyes, Blanca Lucía (Current Proteomics, 2019)
Background: Neuropsychiatric systemic lupus erythematosus or NPSLE, as its name suggests, refers to the neurological and psychiatric manifestations of Systemic Lupus Erythematosus (SLE). In clinical practice, it is often difficult to reach an accurate diagnosis, as this disease presents differently in different patients, and the available diagnostic tests are often not specific enough. Objectives: The aim of this study was to search for proteomic biomarkers in cerebrospinal fluid that could be proposed as diagnostic aids for this disease. Methods: The proteomic profile of cerebrospinal fluid samples of 19 patients with NPSLE, 12 patients with SLE and no neuropsychiatric manifestation (SLEnoNP), 6 patients with neuropsychiatric symptoms but no SLE (NPnoSLE), 5 with Other Autoimmune Disorders without neuropsychiatric manifestations (OADs), and 4 Healthy Controls (HC), were obtained by two-dimensional gel electrophoresis and compared using ImageMaster Platinum 7.0 software. Results: The comparative analysis of the different study groups revealed three proteins of interest that were consistently over-expressed in NPSLE patients. These were identified by mass spectrometry as albumin (spot 16), haptoglobin (spot 160), and beta-2 microglobulin (spot 161). Conclusion: This work is one of the few proteomic studies of NPSLE that uses cerebrospinal fluid as the biological sample. Albumin has previously been proposed as a potential biomarker of rheumatoid arthritis and SLE, which is coherent with these results; but this is the first report of haptoglobin and beta-2 microglobulin in NPSLE, although haptoglobin has been associated with increased antibody production and beta-2 microglobulin with lupus nephritis.
Keywords: proteomics